Atomic habits : tiny changes, remarkable results : an easy & proven way to build good habits & break bad ones - Clear, James (London : Random House Business Books, 2018)
"Atomic habit, noun. Definition: A small habit with big results. People say when you want to change your life, you need to think big: swap job, move house, change partner. But they're wrong. World-renowned life coach James Clear has discovered a completely different way to revolutionise your behaviour. He knows that lasting change comes from hundreds of tiny decisions - doing two push-ups a day, waking up five minutes early, or holding a single short phone call. He calls these atomic habits. Clear delves deep into cutting-edge psychology to explain why your brain is able to amplify such small changes into such big outcomes. He uncovers a handful of simple life hacks (the forgotten art of Habit Stacking, or the unexpected power of the Two-Minute Rule), to show how you too can grow tiny shifts into life-transforming changes in behaviour. And he reveals a simple four-stage method that will let you build atomic habits into your day-to-day life, starting now. These nuclear changes will have an explosive effect on your career, your relationships and your life."--Publisher
Introduction: My story -- The fundamentals: Why tiny changes make a big difference -- The 1st law: Make it obvious -- The 2nd law: Make it attractive -- The 3rd law: Make it easy --The 4th Law: Make it satisfying -- Advanced tactics: How to go from being merely good to being truly great -- Conclusion: The secret to results that last
Originally published: New York : Avery, 2018
Includes bibliographical references (pages 273-298) and index
Keywords: Habit; Habit breaking; Behavior modification; Self-help publications